(2x+44)=(6x-80)

Simple and best practice solution for (2x+44)=(6x-80) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+44)=(6x-80) equation:



(2x+44)=(6x-80)
We move all terms to the left:
(2x+44)-((6x-80))=0
We get rid of parentheses
2x-((6x-80))+44=0
We calculate terms in parentheses: -((6x-80)), so:
(6x-80)
We get rid of parentheses
6x-80
Back to the equation:
-(6x-80)
We get rid of parentheses
2x-6x+80+44=0
We add all the numbers together, and all the variables
-4x+124=0
We move all terms containing x to the left, all other terms to the right
-4x=-124
x=-124/-4
x=+31

See similar equations:

| 40/5x-12=36/30 | | 3(x+9)-(9+x)+6(x+9)=80 | | 2=7/3n-4/3n | | -14x+132=26(x-18 | | 6a-11=5a+9 | | 5/2x+3=12/2 | | 3(-x-1)-7=-8x-40 | | t23=−9 | | 3c-9=-18 | | 3x-5(x-3)=-7+3x-13 | | 2x-6=2x+17 | | 9x+7=-7x-25 | | -5m-4m=63-27 | | 9(x-8)+2=-70 | | 5x-12/40=36/30 | | 8x+10x-2+7=x | | -1(3x-2)=5x+6 | | 9x+10=(7x+9)+(5x-11) | | 4-(x+2)=2x-3x+7 | | 3s-2s=-5 | | -14+6b+7-2b=1+5b | | 5x-2+2x+9=24 | | 14v-6=6-14v | | (x+1)(x+1)=(x+2)(2x)(4) | | -23=1+6x+2x | | 15-8x=-7x+8+8 | | -14+4z=-7z+8 | | (2x+16)=(5x-17) | | (2x+12)+(5x−9)=180 | | 15=k/3-2 | | X-7x+1=-6x+1 | | 15x+36=11x |

Equations solver categories